Un conte de noël [videorecording (DVD)] = A Christmas tale - Desplechin, Arnaud; Deneuve, Catherine, 1943-; Roussillon, Jean-Paul; Amalric, Mathieu, 1965-; Consigny, Anne; Poupaud, Melvil (Criterion collection, 2009)
Junon is the matriarch of the troubled Vuillard family, who come together at Christmas after she learns she needs a bone marrow transplant from a blood relative. The Vuillard's shared history of physical and mental illness, estrangement, self harm, and loss doesn't lead itself to the idea of a cheerful holiday season. Hopefully the Christmastime reunion, a scheme concocted by three of the youngest family members, will finally bring peace to their family.